Regulating assisted reproductive technologies : new horizons / Amel Alghrani. - Alghrani, Amel (Cambridge bioethics and law., 2018)
Reproductive science continues to revolutionise reproduction and propel us further into uncharted territories. The revolution signalled by the birth of Louise Brown after IVF in 1978, prompted governments across Europe and beyond into regulatory action. Forty years on, there are now dramatic and controversial developments in new reproductive technologies. Technologies such as uterus transplantation that may enable unisex gestation and babies gestated by dad; or artificial wombs that will completely divorce reproduction from the human body and allow babies to be gestated by machines, usher in a different set of legal, ethical and social questions to those that arose from IVF. This book revisits the regulation of assisted reproduction and advances the debate on from the now much-discussed issues that arose from IVF, offering a critical analysis of the regulatory challenges raised by new reproductive technologies on the horizon.